Potential of (Citrus nobilis Lour × Citrus deliciosa Tenora) metabolites on COVID-19 virus main protease supported by in silico analysis. Issue 11 (2nd June 2022) - El-Hawary, Seham S.; Issa, Marwa Y.; Ebrahim, Hanaa S.; Mohammed, Anber F.; Hayallah, Alaa M.; El-Kadder, Essam M. Abd; Sayed, Ahmed. M.; Abdelmohsen, Usama Ramadan
Abstract: One of the promising therapeutic strategies for corona virus 2019 (COVID-19) is tolook for enzyme inhibitors. COVID-19 virus main protease (M pro ) plays a vital role in mediating viral transcription and replication, introducing it as an attractive antiviral agent target. LC–ESI–HDMS based metabolic profiling of Citrus nobilis Lour. × Citrus deliciosa Ten. (Rutaceae) annotated 21 compounds belonging to diverse classes. Molecular docking studies were carried out to ascertain the inhibitory action of studied dereplicated compounds through the interactions within the active site of SARS-CoV-2 (M pro ). Among which, quercetin-7- O -glucoside-3- O -rutinoside (21 ) possessed the best binding affinity (–9.47 kcal/mol), followed by luteoline-7-rutinoside (18 ), quercetin-3- O -rutinoside (19 ) and apigenin-8- C -glucoside (15 ) showed less binding affinities ranging at −8.27, −7.97 and −6.94 kcal/mol respectively. Graphical Abstract: UF0001